2004
DOI: 10.1007/bf00167950
|View full text |Cite
|
Sign up to set email alerts
|

Computerized single-breath nitrogen washout: Predicted values in a rural French community

Abstract: Comparative manual and computer measurements of the alveolar N2 slope and closing volumes have indicated systematic differences. When a computerized system is used in field surveys, predicted values are to be obtained under the same conditions. Therefore, we measured the alveolar nitrogen slope (phase III, HID, closing volume (CV), and closing capacity (CC) from single-breath N 2 washout maneuvers in 158 healthy subjects (68 females), ages 21 to 64 years, from a rural community living in a nonpolluted area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
2
7
0
1
Order By: Relevance
“…The CH 4 slope also increased with age. This is consistent with the increased phase III slope during nitrogen washout in the elderly 32 and probably reflects the degenerative changes in the small airways as the individual ages, resulting in increased time constants. The CH 4 slope also was greater in women than in men, but the reason for this is unclear.…”
Section: Discussionsupporting
confidence: 83%
“…The CH 4 slope also increased with age. This is consistent with the increased phase III slope during nitrogen washout in the elderly 32 and probably reflects the degenerative changes in the small airways as the individual ages, resulting in increased time constants. The CH 4 slope also was greater in women than in men, but the reason for this is unclear.…”
Section: Discussionsupporting
confidence: 83%
“…At an age of 70 years, the mean difference in CC between females and males amounts to 2.5% TLC. Using a computerised (automatic) analysis of phase IV, Teculescu et al (1996) found similar results in 158 healthy non-smokers in whom the rate of increase of CC/TLC with age was slightly higher in females than in males, though in this case not significantly. The regression equations of Teculescu et al (1996) Knudson et al (1977) obtained with the single-breath N 2 method were somewhat lower at all ages.…”
Section: Normal Values Of Closing Capacitysupporting
confidence: 53%
“…), and (2) performance of two expirations to RV, which may represent an unbearable burden for subjects who are old and/or sick. In fact Teculescu et al (1996) and Viegi et al (1988) reported that assessment of CC is not ''a useful test for epidemiological purposes'' because of a high task failure rate, especially in elderly subjects. An useful alternative is the assessment of the ''open capacity'' (OC), i.e.…”
Section: Open Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…If the FRC is lower than the CC, the A-a gradient should increase, as some lung units are closed during normal tidal breathing; if the A-a gradient increases sufficiently, the patient is hypoxemic. But measuring closing capacity is difficult and is rarely done, and the equations to predict closing capacity based on age and height have not been sufficiently standardized [13,14].…”
Section: Introductionmentioning
confidence: 99%